Pengolahan Buah Pare (Momordica carantia) Menjadi Nasi Pare yang Baik Dikonsumsi Penderita Diabetes: - M.Faiz Abdillah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Bitter melon is very beneficial for health, especially in the treatment of diabetes. The compounds contained can increase immunity, insulinmimetics, polyphenols which reduce blood glucose. Making bitter melon rice is a simple technological breakthrough to increase consumption of bitter melon more easily and comfortably considering that bitter melon fruit contains quite a lot of sap and a high bitter taste. This journal explains the processing of bitter melon fruit into bitter melon rice which is more practical for general consumption, especially for diabetes sufferers. Making bitter melon rice requires that the bitter melon fruit is still green because it contains momorcidin and other compounds which are still abundant and have not undergone a ripening process. Making bitter melon rice can be done by mixing fruit that has been washed and soaked in salt water, then mashing the bitter melon fruit with sago flour then steaming and cutting it into small pieces resembling rice. The results obtained from the nutritional value of processing bitter melon fruit into rice are known to have a higher fiber content and lower calorie and sugar value compared to rice and this is very good, apart from that the carbohydrate content of bitter melon fruit after being processed into bitter melon rice is 20.22 g lower with The carbohydrate value of rice is 39.8 g per 100 grams, therefore bitter melon rice is very good for consumption by diabetics.